Enso influence on water vapor transport and thermodynamics over Northwestern South America (2024)
The interannual variability of hydroclimatic conditions in Northwestern South America, especially precipitation, is mainly influenced by the El Niño–Southern Oscillation (ENSO). We explore potential mechanisms that affect precipitation occurrence in Northwestern South America during El Niño and La Niña events over the period 1980–2019, using data from the ERA5 reanalysis. We look at the atmospheric moisture contribution from different sources using the Dynamic Recycling Model to track water vapor trajectories. Interestingly, conditions with reduced precipitation during El Niño events can take place along with increased precipitable water. To understand this, we analyze thermodynamic conditions in the atmosphere that are necessary for precipitation to occur over the region, such as convective available potential energy, convective inhibition, lifting condensation level, and low-level relative humidity. With this approach, we find more favorable thermodynamic conditions for the occurrence of precipitation during La Niña events, even if the content of water vapor is equal or even less than during El Niño events. We also look at the structure of the regional Hadley and Walker circulation in both types of events and find that a weaker ascending motion during El Niño events also inhibits convection. This study provides an integral picture of how precipitation anomalies over Northwestern South America during ENSO events are related to dynamic and thermodynamic conditions and sources of atmospheric moisture.